Brazilian Clinical Strains of Actinobacillus pleuropneumoniae and Pasteurella multocida: Capsular Diversity, Antimicrobial Susceptibility (In Vitro) and Proof of Concept for Prevention of Natural Colonization by Multi-Doses Protocol of Tildipirosin - Suzana Satomi Kuchiishi; Simone Ramos Prigol; Eduarda Bresolin; Bianca Fernandes Lenhard; Caroline Pissetti; María-José; César-Bernardo Gut; Sonia Martínez-Martínez; Luiz Carlos Kreutz; Rafael Frandoloso (MDPI AG, 2023)
One hundred Actinobacillus pleuropneumoniae (App) and sixty Pasteurella multocida subsp. multocida serogroup A (PmA) isolates were recovered from porcine pneumonic lungs collected from eight central or southern states of Brazil between 2014 and 2018 (App) or between 2017 and 2021 (PmA). A. pleuropneumoniae clinical isolates were typed by multiplex PCR and the most prevalent serovars were 8, 7 and 5 (43, 25% and 18%, respectively). In addition, three virulence genes were assessed in P. multocida isolates, all being positive to capA (PmA) and kmt1 genes, all negative to capD and toxA, and most of them (85%) negative to pfhA gene. The susceptibility of both pathogens to tildipirosin was investigated using a broth microdilution assay. The percentage of isolates susceptible to tildipirosin was 95% for App and 73.3% for PmA. The MIC50 values were 0.25 and 1 μg/mL and the MIC90 values were 4 and >64 μg/mL for App and PmA, respectively. Finally, a multiple-dose protocol of tildipirosin was tested in suckling piglets on a farm endemic for both pathogens. Tildipirosin was able to prevent the natural colonization of the tonsils by App and PmA and significantly (p < 0.0001) reduced the burden of Glaesserella parasuis in this tissue. In summary, our results demonstrate that: (i) tildipirosin can be included in the list of antibiotics to control outbreaks of lung disease caused by App regardless of the capsular type, and (ii) in the case of clinical strains of App and PmA that are sensitive to tildipirosin based on susceptibility testing, the use of this antibiotic in eradication programs for A. pleuropneumoniae and P. multocida can be strongly recommended.